WILL YOU CARE FOR ME: PROTOCOL AND BASELINE CHARACTERISTICS OF THE PILOT CARDIOLOGY-RENAL-METABOLIC (CaReMe) INTEGRATED CLINIC IN MALAYSIA - Sarvanandan, Tharsini; Khoo, Jun Kit; Ooi, Ying Guat; Lim, Lee-Ling; Lim, Soo Kun; Ooi, Shok Hoon; Chew, Chang Chuan; Yew, Soo Ying; Em, Jun Min; Chee, Kok Han; New, Ru Peng; Ismail, Izzah Nazura; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION At least one in three Malaysians living with type 2 diabetes (T2D) develops cardio-renal complications. Current management strategies are fragmented. The pilot, Cardiology-Renal-Metabolic (CaReMe) Clinic in Malaysia, aims to integrate care of patients with T2D by focusing on patient-centred, guideline-directed medical therapy (GDMT) use. METHODOLOGY This is a pilot CaReMe clinic in Southeast Asia that was established at our centre. Patients with T2D and renal or cardiovascular complications were recruited for weekly virtual clinics. These clinics involve multidisciplinary meetings between cardiology, nephrology, and endocrinology specialists. Patients' cases and current issues were highlighted, medications reviewed, and management plans formulated. Patients were followed up every six months with data collected at baseline and every six months for two years to assess metabolic, cardiovascular, and renal outcomes, including patient-related quality-of-life measures (SF 12). Patients in the CaReMe cohort were compared against standard care by propensity score matching methods. RESULT One hundred forty-two patients have been recruited (mean age: 62.9 ± 11.4 years, 55.6% men). The mean baseline HbA1c was 8.9 ± 1.7 %, with a mean duration of diabetes of 18.2 ± 10.0 years. The mean BMI and waist circumference were 29.6 ± 6.9 kg/m2 and 101.5 ± 15.3 cm, respectively. Majority of patients had hypertension (96.4%) and dyslipidaemia (95.0%). In terms of ASCVD, 28.2% had coronary artery disease, 12.0% had stroke, while 2.8% had peripheral arterial disease. Within this cohort, 66.2% had CKD with a mean eGFR of 61.4 ± 30.5 mL/min/1.73 m2 and a median uACR of 30.8 (6.05 – 111.3) mg/mmol. 19.4% had heart failure, 16.2% had retinopathy, and 3.5% had peripheral neuropathy. A large proportion of patients were on insulin (71.1%), and GDMT uptake were as follows: SGLT2- inhibitors (90.1%), GLP1-RA (28.1%), RAAS-blockade (88.0%), and statins (93.0%). CONCLUSION The pilot Malaysian CaReMe clinics adopt a holistic, patient-centred implementation of integrated care to address gaps and improve outcomes in T2D. These virtual multidisciplinary clinics can easily be implemented within resource-limited settings.